Who Needs Good Neighbors?. (April 2015) - Howley, Peter; Neill, Stephen O; Atkinson, Rowland
Due to the increasing spatial dispersion of social networks, the association between neighbor relationships and quality of life has become more uncertain. Our analysis used instrumental variable modelling to reduce bias associated with residual confounding and reverse causation, in order to provide a more reliable examination of the effect of interaction with neighbors on subjective well-being than previous work. While the frames of reference for individuals' socialising may have shifted outside the neighborhood, our analysis provides robust evidence that interaction with neighbors still matters a great deal for subjective well-being. A further important question to ask is if neighboring does affect well-being, then are there certain groups in society for whom contact with neighbors matters more? Our analysis suggests that there are, namely for those in a relationship, unemployed or retired. This means that while fostering contact with neighbors has the potential to significantly improve individual well-being, such policy efforts are likely to matter a good deal more in neighborhoods with relatively large numbers of geographically constrained social groups, such as the elderly and the unemployed.